A contribuição do “Espaço Cultural Nossa Biblioteca” para o desenvolvimento sociocultural do usuário - COSTA, Maria Nazaré Rodrigues da (2017)
It perform a case study at the "Espaço Cultural Nossa Biblioteca" located at Guamá neighbourhood of. It represent the contribuition of this community library to the user cultural development. It ia a qualitative research, were used in the case study as instrument for collecting data, questions and also a recorder, the first was applied to seven users of the library, and second to the coordinators ar (ECNB). Was analyzed the collected data regard the users opinion about how the library has contrituted for their cultural formations.The result we reach was that the work's goal is to show the contribuition for the community wich is inserterdwas achieved.